Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1101/467787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Core components of endosomal mRNA transport are evolutionarily conserved in fungi

Abstract: † equal contribution Running title: Endosomal mRNA transport is conserved Word count: 1280 words with 7618 characters AbstractActive movement of mRNAs by sophisticated transport machineries determines precise spatiotemporal expression of encoded proteins. A prominent example discovered in fungi is microtubule-dependent transport via endosomes. This mode of transport was thought to be only operational in the basidiomycete Ustilago maydis. Here, we report that distinct core components are evolutionarily conserve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…We observed extensive co-localization in processively moving units, suggesting that the RNA-binding protein GUL1 participates in endosomal mRNA transport (Fig 7C-D; S4 movie). Importantly, this is the first evidence that this mode of long-distance transport is also present in ascomycetes (42). Taken together, our fluorescent microscopic investigation reveals that GUL1 acts close to nuclei and shuttles with PAB1 and transport endosomes along microtubules.…”
Section: B S5 Fig)supporting
confidence: 66%
See 1 more Smart Citation
“…We observed extensive co-localization in processively moving units, suggesting that the RNA-binding protein GUL1 participates in endosomal mRNA transport (Fig 7C-D; S4 movie). Importantly, this is the first evidence that this mode of long-distance transport is also present in ascomycetes (42). Taken together, our fluorescent microscopic investigation reveals that GUL1 acts close to nuclei and shuttles with PAB1 and transport endosomes along microtubules.…”
Section: B S5 Fig)supporting
confidence: 66%
“…Transport mRNPs are stabilized by the scaffold protein Upa2 and linked to endosomes via the FYVE domain protein Upa1 (41,46). A phylogenetic analysis revealed that important core components of endosomal transport like Upa2 and the key RBP Rrm4 are missing in ascomycetes (42). However, here we demonstrate that numerous RNA-binding proteins containing RRM domains are prominent STRIPAK targets.…”
Section: Gul1 Is Trafficking On Endosomesmentioning
confidence: 63%
“…We observed extensive co-localization in processively moving units of about 91%, suggesting that the RNA-binding protein GUL1 participates in endosomal mRNA transport ( Fig 8 ; S9 Movie , S5 Dataset ). Importantly, this is the first evidence that this mode of long-distance transport is also present in a euascomycete [ 52 ]. Taken together, our fluorescent microscopic investigation reveals that GUL1 acts close to nuclei and shuttles with Pab1 most likely on Rab5-positive-endosomes along microtubules.…”
Section: Resultsmentioning
confidence: 95%
“…Transport mRNPs are stabilized by the scaffold protein Upa2 and linked to endosomes via the FYVE domain protein Upa1 [ 51 , 56 ]. A phylogenetic analysis revealed that important core components of endosomal transport like Upa2 and the key RBP Rrm4 are missing in ascomycetes [ 52 ]. However, here we demonstrate that numerous RNA-binding proteins containing RRM domains are prominent STRIPAK targets.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the notion that Rrm4, Upa1 and Upa2 function together, these fungi also had orthologs for Rrm4 and Upa1. Notably, Upa2 was absent in Malassezia globosa , which presumably has lost the endosomal mRNA transport machinery, because it lacks a clear ortholog of Rrm4 (Fig C) . In essence, the evolutionarily conserved Upa2 is a novel factor essential for efficient unipolar growth that might function in endosomal mRNA transport.…”
Section: Resultsmentioning
confidence: 99%